LOS DESAFÍOS DE LA INCORPORACIÓN DE TIC EN LA EDUCACIÓN UNIVERSITARIA - Fabro, Ana Patricia (Universidad Nacional del Litoral, 2020)
At present, educational institutions face the challenge of ICT incorporation to their learning activities. This occurs in the framework of the “society of knowledge” where education, instead of being classic and conservative as usual, requires active pedagogical approaches that facilitate the act “learn to learn” as well as dynamic and creative environments. In this context, interactive media in education enable the transformation of information into knowledge through the acquisition of the corresponding competences. Current educational trend is based on the elaboration of interactive systems that prepare students for reasoning and solving problems, and leave behind traditional models of teaching, particularly those that are centred on passive knowledge reception.